THE EFFECTIVENESS OF SCHOOL-BASED DRUG RESISTANCE EDUCATION PROGRAM IN THE UNITED STATES - Sahin, Ismail; Karapazarlioglu, Ersin (European Scientific Journal, ESJ, 2014)
There are two major approaches to overcome drug problems: supply reduction and demand reduction. Supply reduction strategy is implemented by law enforcement agencies and aims to constrict the supply by disrupting the illicit drug market and preventing drug distribution in the society On the other hand, demand reduction strategy implemented through treatment and education aims to reduce the demand on drug. Many researchers emphasize that the best way to curb drug abuse is to target youth and prevent them from initiating drug use at an early age before getting in contact with drug. In many countries, reports show that young people start drug use as early as age 15. Therefore, most drug prevention programs target young people while in school. This is very important due to the fact that young people starting drug abuse at early age are more likely to use more dangerous drugs and become persistent addicts. This study briefly explains the main drug control strategies and then discusses the theoretical framework behind the schoolbased drug education programs. In the following paragraphs, the authors aim to make an in-depth analysis of the studies that examine the effectiveness of the school-based drug resistance education programs in the US.